Applying Reciprocal Questioning (ReQuest) to Improve Students’ Critical Reading Ability - Reni Sapitri; Teguh Satria Amin (Jurnal Studi Guru dan Pembelajaran, 2018)
The objective of the research was to investigate the improvement of critical reading skills in reading by the English students through reciprocal questioning (ReQuest). The respondents consisted of 25 students from the VII grade in 2017/2018 academic year. The data were collected through reading tests, observation, and interview. The result indicated that the application of reciprocal questioning strategy significantly improve the critical reading ability of the students as reflected in pre-test and post-test in cycle 1 and cycle 2: 9.8; 16.04; and 17.64. The findings were supported by the respondents’ positive attitudes as reflected in the interviews.